IDENTIFICATION OF MELANOCORTIN 1 RECEPTOR (MC1R) GENE BASED ON COAT COLOR OF BALI COWS OF KUPANG BY USINGTHE PCR-RFLP METHOD - Tabun, A.C.; Hartatik, T.; Sumadi, S. (Diponegoro University, 2013)
The objective of this study was to identify the Melanocortin 1 Receptor (MC1R) gene in sorrel-,black- and white-Bali cows originated from Kupang-East Nusa Tenggara. Blood samples were takenfrom 46 cows consisted of of 17, 18 and 8 of sorrel, black and 8 heads, respectively, and 3 heads of bull.The PCR-RFLP method was performed to identify the gene. Amplification of PCR gene MC1R ofKupang's Bali Cattle (KBC) was 296 bp. The digestion by using MspI enzyme showed that there wereEE genotype (169, 136 bp) in Bali bull, sorrel and white cows. Two 2 genotypes, those were EE (169,136 bp) and Ee (296, 169, 136 bp) were found in black Bali cow. The frequency of E alele of KBC was0.99 (99%) and e alele was 0.01 (1%). MC1R gene in KBC was monomorphic and the it can be used asthe marker of the coat color in the population.